SISTEMA DE EJERCICIOS PARA EL DESARROLLO DE LA RESISTENCIA A LA FUERZA RÁPIDA EN LOS LUCHADORES DEL ESTILO LIBRE DE LA CATEGORÍA MENOR 14- 15 AÑOS DE LA FEDERACIÓN DEPORTIVA DE LOS RÍOS - REYES SANCHEZ DARLING JOSUE (2024)
The present research entitled. EXERCISE SYSTEM FOR THE DEVELOPMENT OF RESISTANCE TO RAPID FORCE IN FREESTYLE WRESTLERS OF THE MINOR CATEGORY 14-15 YEARS OF THE LOS RÍOS SPORTS FEDERATION has as its fundamental objective of Sports Wrestling, is to improve the health and strengthen the organism of athletes so that they can assimilate with greater quality the practical contents of the preparation of athletes in a progressive, systematic, staggered manner, according to levels and categories, so that they can obtain high sporting results. In recent times, substantial changes have occurred in the theory and methodology, and in the practice of fighting. The systematic and impetuous development of this sport in recent years, especially as a result of the great boom achieved by the results of international competitions and competitions, has forced our specialists, in a more in-depth way, to study and sometimes to review some issues of this theory and methodology and the practice of sports fighting. Today, science and technology have advanced enough to develop objective methods to observe, plan and investigate different aspects of physical preparation, training theory and methodology. Motor skills are naturally improved during training for the physical preparation of the fighter, although it is important to consider that not all physical development approaches are suitable for the current training demands of athletes. Therefore, it is essential to use those resources that best fit the needs of the conflict, using the methods, practices and complementary disciplines that we consider can favor the development of these skills in a more efficient, faster and more precise way. The work presents exercises that can respond to the possibility of development with the proposed means.